Inactivation of interleukin-30 in colon cancer stem cells via CRISPR/Cas9 genome editing inhibits their oncogenicity and improves host survival. Issue 3 (16th March 2023) - D'Antonio, Luigi; Fieni, Cristiano; Ciummo, Stefania Livia; Vespa, Simone; Lotti, Lavinia; Sorrentino, Carlo; Di Carlo, Emma
Abstract : Background: Progression of colorectal cancer (CRC), a leading cause of cancer-related death worldwide, is driven by colorectal cancer stem cells (CR-CSCs), which are regulated by endogenous and microenvironmental signals. Interleukin (IL)-30 has proven to be crucial for CSC viability and tumor progression. Whether it is involved in CRC tumorigenesis and impacts clinical behavior is unknown. Methods: IL30 production and functions, in stem and non-stem CRC cells, were determined by western blot, immunoelectron microscopy, flow cytometry, cell viability and sphere formation assays. CRISPR/Cas9-mediated deletion of the IL30 gene, RNA-Seq and implantation of IL30 gene transfected or deleted CR-CSCs in NSG mice allowed to investigate IL30's role in CRC oncogenesis. Bioinformatics and immunopathology of CRC samples highlighted the clinical implications. Results: We demonstrated that both CR-CSCs and CRC cells express membrane-anchored IL30 that regulates their self-renewal, via WNT5A and RAB33A, and/or proliferation and migration, primarily by upregulating CXCR4 via STAT3, which are suppressed by IL30 gene deletion, along with WNT and RAS pathways. Deletion of IL30 gene downregulates the expression of proteases, such as MMP2 and MMP13, chemokine receptors, mostly CCR7, CCR3 and CXCR4, and growth and inflammatory mediators, including ANGPT2, CXCL10, EPO, IGF1 and EGF. These factors contribute to IL30-driven CR-CSC and CRC cell expansion, which is abrogated by their selective blockade. IL30 gene deleted CR-CSCs displayed reduced tumorigenicity and gave rise to slow-growing and low metastatic tumors in 80% of mice, which survived much longer than controls. Bioinformatics and CIBERSORTx of the ' Colorectal Adenocarcinoma TCGA Nature 2012 ' collection, and morphometric assessment of IL30 expression in clinical CRC samples revealed that the lack of IL30 in CRC and infiltrating leucocytes correlates with prolonged overall survival. Conclusions: IL30 is a new CRC driver, since its inactivation, which disables oncogenic pathways and multiple autocrine loops, inhibits CR-CSC tumorigenicity and metastatic ability. The development of CRISPR/Cas9-mediated targeting of IL30 could improve the current therapeutic landscape of CRC.